TESTOSTERONE AND COGNITIVE FUNCTION (British Journal of Global Ecology and Sustainable Development, 2025)
Testosterone, a crucial androgen hormone, plays a significant role in cognitive health across all life stages. During prenatal and early development, testosterone influences corticohippocampal maturation, essential for spatial and executive functions. Adolescence is marked by enhanced visuospatial and decision-making abilities linked to elevated testosterone levels, though excess may lead to impulsivity. In adulthood, balanced testosterone positively impacts memory, verbal fluency, and decision-making. Conversely, age-related testosterone decline is associated with increased risks of dementia and Alzheimer’s disease.